2020
DOI: 10.1101/2020.08.28.270785
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Racing against stomatal attenuation: rapid CO2response curves more reliably estimate photosynthetic capacity than steady state curves in a low conductance species

Abstract: A/Ci curves are an important gas-exchange-based approach to understanding the regulation of photosynthesis, describing the response of net CO2 assimilation (A) to leaf internal concentration of CO2 (Ci). Low stomatal conductance species pose a challenge to the measurement of A/Ci curves by reducing the signal-to-noise ratio of gas exchange measures. Additionally, the stomatal attenuation effect of elevated ambient CO2 leads to further reduction of conductance and may lead to erroneous interpretation of high Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…RACiR curves are a novel technique that have been used successfully to rapidly acquire gas exchange data for the estimation of V cmax and J max while simultaneously overcoming the issues of stomatal attenuation and changes in enzyme kinetics that are characteristic of the traditional A : C i curve (Stinziano et al 2017 , 2019 ; Coursolle et al 2019 ; Vincent et al 2020 ). RACiR curves, Laisk curves, and point measures of chlorophyll fluorescence showed that differences in assimilation between wild and domestic rice during long- or short-term heat exposure could not be explained by differences in photorespiration, respiration or ETR (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…RACiR curves are a novel technique that have been used successfully to rapidly acquire gas exchange data for the estimation of V cmax and J max while simultaneously overcoming the issues of stomatal attenuation and changes in enzyme kinetics that are characteristic of the traditional A : C i curve (Stinziano et al 2017 , 2019 ; Coursolle et al 2019 ; Vincent et al 2020 ). RACiR curves, Laisk curves, and point measures of chlorophyll fluorescence showed that differences in assimilation between wild and domestic rice during long- or short-term heat exposure could not be explained by differences in photorespiration, respiration or ETR (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that V cmax andJ max calculated by RACiR curves under multiple [CO 2 ] gradients were not significantly different from TACiR curves, indicating that the RACiR technique could be applied to herbs as well as evergreen species (Pilon et al 2018, Lu et al 2020, McKenzie-Gopsill et al 2020, Vincent et al 2020, Liu and van Iersel 2021 and thus is likely to be generalizable among different plant life forms.…”
Section: Racir Technique Could Be Applied To Evergreens and Herbsmentioning
confidence: 71%
“…This result indicated that RACiR curves with high monotonic increase but not down-up ramp [CO 2 ] (e.g., R1) might be an inadvisable choice for C. nocturnumconsidering that the cuticle of papery leaves was usually thinner with lower stomatal density than those of leathery leaves (Ma 2005). However, Vincent et al (2020) set [CO 2 ] at 100-900 ppm (100 ppm min -1 , 8 minutes) for Citrus sinensis (L.) Valencia, a species with low stomatal conductance, and theV cmax and J max obtained using RACiR curves were not significantly different from TACiR curves. Thus, we speculate that setting monotonically increasing [CO 2 ] too high (e.g., >1000 ppm) in RACiR curves may not be applicable to low stomatal conductance species, although Sharkey (2019) argued that a continuous and rapid increase of [CO 2 ] was the best when measuring TACiR curves.…”
Section: Racir Technique Could Be Applied To Evergreens and Herbsmentioning
confidence: 97%